Pay for percentile - Gadi Barlevy; Derek Neal (Institute for the Study of Labor (IZA), 2009)
We propose an incentive pay scheme for educators that links educator compensation to the ranks of their students within appropriately defined comparison sets, and we show that under certain conditions our scheme induces teachers to allocate socially optimal levels of effort to all students. Because this scheme employs only ordinal information, our scheme allows education authorities to employ completely new assessments at each testing date without ever having to equate various assessment forms. Thus, our scheme removes incentives for teachers to teach to a particular assessment form and eliminates any opportunities to influence reward pay by corrupting the equating process or the scales used to report assessment results. Having shown that cardinal measures of achievement growth over time are not a necessary ingredient of incentive systems for educators, we note that education authorities can employ our scheme as a means of providing incentives for educators while employing a separate system for measuring growth in student achievement that involves no stakes for educators. This approach creates no incentives for educators to take actions that contaminate the measurement of student progress.
urn:nbn:de:101:1-200910086458
Keywords: J33; I20; 330; Compensation; education; tournaments; Lehrkräfte; Leistungsorientierte Vergütung; Bildungsniveau; Extensives Spiel; Theorie